Multistep taphonomic alterations in fluvial mollusk shells: a case study in the touro passo formation (pleistocene–holocene), Southern Brazil - Erthal, Fernando; Kotzian, Carla B.; Simões, Marcello Guimarães [UNESP] (Sepm-soc Sedimentary Geology, 2015)
Accurate paleoenvironmental reconstruction relies on the correct interpretation of the postmortem history of skeletal remains in shelly assemblages. In contrast to marine settings, actualistic taphonomic studies are lacking for shell-rich concentrations in freshwater riverine systems. In particular, the taphonomic pathways and the origins of taphonomic signatures that are recorded in bioclasts from fluvial settings are poorly known. In this study, we addressed this issue by comparing the taphonomic signatures and shell-damage profiles among shells of freshwater mollusks recorded both in death and in fossil assemblages from the same fluvial environment. Our data indicated that dissolution was the most pervasive taphonomic process leading to the destruction of the shells. The loss of taphonomic information extended beyond shell dissolution in the riverbed, or the early diagenesis in the sedimentary record. The loss of biological information from the living community through the death assemblage, until the incorporation of shells as fossils, mainly occurred during the time the shells were in the sediment-water interface. Though this destruction affected primarily dead shells, reworked fossils also became vulnerable because they were carried out into the river load again by channel avulsion. A model that included the main taphonomic pathways followed by the molluscan shells in the fluvial Touro Passo Formation (Pleistocene-Holocene) is discussed. In this model, two main destructive domains were recognized, which were the biological, physical, and chemical processes operating at the taphonomically active zone (= TAZ domain) and the pedogenetic domain.